The Protective Role of Nigela Sativa Volatile Oil on Antioxidant and Oxidative Stress Enzymes - Ahmed, Ahmed Tawfeeq; Hameed, Inas Hazim; Hameed, Walaa Hazim (Universitas Muhammadiyah Sidoarjo, 2024)
Hepatotoxicity is the outcome of a paracetamol overdose.In this study, 40 adult male rats, weighing 180–260 gm and aged between 9 and 13 weeks, were given doses of Nigela sativa oil and their liver enzymes were examined to see how paracetamol affected them. The rats were kept in an environment at a temperature of 25 Co in an animal house. ,There were four groups of rats, and food was provided for them. (G). (G1) The only injections given to the control group are food and regular saline (0.9% of the time). (G2) 200 mg/kg of N. sativa and (G3) 400 mg/kg of paracetamol Addition of 400 mg/kg body weight of paracetamol. supplying 300 mg/kg B.W. of N. sativa to (G4)400 milligrams/kg B.W. of aspirin. Rat G2, GPT 87.80 IUL, and GOT hepatic enzyme concentration (129.32 IUL) all exhibit significant increases in comparison to the control. Furthermore, the levels of the liver GSH enzyme in rats (G2 )1.24 IUL shown a substantial increase, whereas G3 ( GOT ) 91.9 IUL, (GPT )76.70 IUL, and group (G4) GOT 109.88 IUL and enzyme (GPT ) 55.66 IUL exhibited significant declines as compared with control. While MDA enzyme in rats G2 (0.259 IUL) shows a major increase in comparison to the control, rats G3 (0.139 IUL) and G4 (0.112) show a noticeable decrease in comparison to G2. While body weight indicates that G2's outcomes are significantly lower than those of the other three groups. Groups G3 (2.55 gm) and G4 (2.7 gm) demonstrated a significant rise in liver weight compared to controls and G2, whereas groups G2 (24.23 gm) demonstrated a significant increase in liver weight compared to controls and group G2. Male rats in groups G2 (1.7 gm) demonstrated a significant drop in liver weight compared to controls.